A Study on Safety Management Plan for Recycling of Medium-Contact Wastes via Ecotoxicity Assessment. (July 2022) - Hong, Soo-Yeon; Yoon, Cheol-Woo; Yoon, Young-Sam; Kang, Jang-Hyun; Jeon, Tae-Wan
In South Korea, hazardous characteristics of wastes to be recycled are managed through the "Environmental Impact Assessment of Recycling" system. The ecotoxicity of medium-contact recyclable wastes, that is, those in contact with soil, groundwater, surface water, etc., is managed according to this system and is determined based on whether or not they exceed an ecotoxicity value (TU) of 2.0. The ecotoxicity of wastes is tested and determined by using pretreated eluate samples according to the Official Wastes Test Standard and applying the Official Water Pollution Process Test Standard. However, no ecotoxicity management limits are stipulated for medium-contact recycling using wastes in numerous other countries. This study aims to evaluate applicability and safety of the ecotoxicity test for wastes used in medium-contact recycling and establish an efficient management plan for hazardous characteristic wastes. Target wastes for the survey were selected based on the Wastes Control Act in South Korea. Nine types of waste were selected, which are representative types of wastes to which ecotoxicity is applied. In order to secure the representativeness of the target samples, a total of 45 samples were collected by selecting 5 cases each of the 9 waste types in consideration of the type of industry and amount of waste generated. Limit exceedance was calculated for each category of hazardous substances (leaching, total content), pH, and ecotoxicity of a total of 45 samples, and was found to increase in the order of leaching 2.22% < pH 9.09% < content 31.11% < ecotoxicity 37.21%. This indicates that the limit exceedance was maximum in the ecotoxicity category. Therefore, the application of ecotoxicity limit is efficient for identifying and comprehensively managing the environmental impacts of various types of hazardous substances contained in wastes from the perspective of comprehensive toxicity.